In situ helicity inversion of self-assembled nano-helices. Issue 17 (28th November 2014) - Tamoto, Rumi; Daugey, Nicolas; Buffeteau, Thierry; Kauffmann, Brice; Takafuji, Makoto; Ihara, Hirotaka; Oda, Reiko
Abstract : The handedness of nanometrical self-assembled helices was inverted when these helices were in contact with an excess solution of chiral anions with opposite enantiomers. An important difference in the kinetics of chirality inversion at the molecular level and mesoscopic level was observed. Abstract : The handedness of nanometrical helices based on surfactant assemblies was inverted when these helices were in contact with an excess solution of chiral anions with opposite enantiomers. An important difference in the kinetics of chirality inversion at the molecular level and mesoscopic level was observed.